2008
DOI: 10.1007/s10646-008-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: structure, properties, preparation and behaviour in environmental media

Abstract: There is increasing interest and need to develop a deeper understanding of the nature, fate and behaviour of nanoparticles in the environment. This is driven by the increased use of engineered nanoparticles and the increased pressure to commercialise this growing technology. In this review we discuss the key properties of nanoparticles and their preparation and then discuss how these factors can play a role in determining their fate and behaviour in the natural environment. Key focus of the discussion will rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
348
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(360 citation statements)
references
References 102 publications
3
348
0
9
Order By: Relevance
“…This was reflected in low measured Ti concentrations in the water column compared to the nominal concentrations. This is in accordance with previous studies that showed the aggregation of uncoated ENPs in environments with higher ionic strength, and aggregates formed by uncoated TiO2NP are assumed to be highly bioavailable for filter feeding organisms such as M. edulis (Canesi et al, 2012;Christian et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This was reflected in low measured Ti concentrations in the water column compared to the nominal concentrations. This is in accordance with previous studies that showed the aggregation of uncoated ENPs in environments with higher ionic strength, and aggregates formed by uncoated TiO2NP are assumed to be highly bioavailable for filter feeding organisms such as M. edulis (Canesi et al, 2012;Christian et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Which techniques are appropriate will depend largely on the sample type, property of interest, and analytical method to be used. Nanoparticulate systems are extremely sensitive to perturbation from factors such as pH, ionic strength, sunlight, bacterial growth, and temperature; and they are almost never in thermodynamic equilibrium [4]. In some cases, sample preservation may not be possible for a given property of interest that must be analyzed, such as aggregation state.…”
Section: Sample Collection Preparation Preservation and Storagementioning
confidence: 99%
“…Nanoparticles (NPs) are defined as particulate matter with at least one dimension less than 100 nm [1]. Although materials of this size are naturally present in the environment, manufactured NPs may have distinctive surface properties and chemistry in comparison with natural NPs [2].…”
Section: Introductionmentioning
confidence: 99%